Calretinin and calbindin D28k have different domain organizations - Palczewska, Małgorzata (Cold Spring Harbor Laboratory Press, 2003)
The domain organization of calretinin (CR) was predicted to involve all six EF-hand motifs (labeled I to VI) condensed into a single domain, as characterized for calbindin D28k (Calb), the closest homolog of calretinin. Unperturbed (1)H,(15)N HSQC NMR spectra of a (15)N-labeled calretinin fragment (CR III–VI, residues 100–271) in the presence of the unlabeled complimentary fragment (CR I–II, residues 1–100) show that these fragments do not interact. Size exclusion chromatography and affinity chromatography data support this conclusion. The HSQC spectrum of (15)N-labeled CR is similar to the overlaid spectra of individual (15)N-labeled CR fragments (CR I–II and CR III–VI), also suggesting that these regions do not interact within intact CR. In contrast to these observations, but in accordance with the Calb studies, we observed interactions between other CR fragments: CR I (1–60) with CR II–VI (61–271), and CR I–III (1–142) with CR IV–VI (145–271). We conclude that CR is formed from at least two independent domains consisting of CR I–II and CR III–VI. The differences in domain organization of Calb and CR may explain the specific target interaction of Calb with caspase-3. Most importantly, the comparison of CR and Calb domain organizations questions the value of homologous modeling of EF-hand proteins, and perhaps of other protein families.